Hubungan Dukungan Keluarga Dengan Kualitas Hidup Pada Lansia Di Wilayah Kerja Puskesmas Samata Kabupaten Gowa - fitriani, aidah; Syisnawati, Syisnawati; Sutria, Eny; Yulianti Syam, Ghina Syafira (Alauddin Scientific Journal of Nursing, 2024)
The final stage of the life process is called the elderly, at this time a person experiences changes that result in bio, psycho, social, and spiritual declines that occur naturally due to the aging process. This decline in function can affect the quality of life of the elderly, one of the factors that can affect the quality of life of the elderly is family support. The purpose of this study was to determine the relationship between family support and the quality of life of the elderly in the working area of ​​the Samata Public Health Center, Gowa Regency. The design in this research is descriptive correlation with cross sectional approach. The sample used in this study was the elderly as many as 94 people. The instruments used in this study were family support questionnaires and WHOQL-OLD. Data were analyzed using chi square test. The results of the study found that there was a relationship between family support and the quality of life of the elderly with p = 0.000. This means that there is a significant relationship between family support and the quality of life of the elderly in the Samata Health Center Working Area. The conclusion of this study is that good family support can improve the quality of life of the elderly. Therefore, families are expected to provide support to the elderly so that they have a good quality of life. Keywords: Family Support, Quality of Life for the Elderly